Transcriptome and proteome analyses and the role of atypical calpain protein and autophagy in the spliced leader silencing pathway in Trypanosoma brucei. Issue 1 (31st August 2016) - Hope, Ronen; Egarmina, Katarina; Voloshin, Konstantin; Waldman Ben‐Asher, Hiba; Carmi, Shai; Eliaz, Dror; Drori, Yaron; Michaeli, Shulamit
Summary: Under persistent ER stress, Trypanosoma brucei parasites induce the spliced leader silencing (SLS) pathway. In SLS, transcription of the SL RNA gene, the SL donor to all mRNAs, is extinguished, arresting trans ‐splicing and leading to programmed cell death (PCD). In this study, we investigated the transcriptome following silencing of SEC63, a factor essential for protein translocation across the ER membrane, and whose silencing induces SLS. The proteome of SEC63 ‐silenced cells was analyzed with an emphasis on SLS‐specific alterations in protein expression, and modifications that do not directly result from perturbations in trans‐ splicing. One such protein identified is an atypical calpain SKCRP7.1/7.2 . Co‐silencing of SKCRP7.1/7.2 and SEC63 eliminated SLS induction due its role in translocating the PK3 kinase. This kinase initiates SLS by migrating to the nucleus and phosphorylating TRF4 leading to shut‐off of SL RNA transcription. Thus, SKCRP7.1 is involved in SLS signaling and the accompanying PCD. The role of autophagy in SLS was also investigated; eliminating autophagy through VPS34 or ATG7 silencing demonstrated that autophagy is not essential for SLS induction, but is associated with PCD. Thus, this study identified factors that are used by the parasite to cope with ER stress and to induce SLS and PCD. Abstract : Spliced leader silencing (SLS) is a stress induced mechanism in Trypanosoma brucei which stops SL RNA transcription and trans‐ splicing. The study describes the proteome and transcriptome of SLS induced cells and identified a key protein in SLS signaling, a calpain like‐protease which is important for transmitting the stress signal to the nucleus and for dying in a controlled way. Autophagy also contributes to programmed cell death induced by SLS induction.